1997
DOI: 10.1021/bk-1997-0657.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Fluorescent Immunoassays: A Novel Approach to Environmental Analysis

Abstract: The near-infrared (NIR) region of spectrum provides many advantages over conventional UV--visible region and is particularly useful when background interference is the primary concern. Many NIR fluorophores have high molar absorptivities and fluorescence quantum yields. The use of laser diodes for excitation and photodiodes for detection makes the NIR fluorophores an ideal choice as tracers for various applications. NIR fluorescence immunoassays (NIRFIAs) for disease-related antigens have been developed and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The development of functional dyes that absorb and emit in the red visible or near‐infrared (NIR) region of the optical spectrum has received increasing attention in the last decade. Although there has been considerable interest in NIR dyes since the early/middle of the last century,1 from advances in photography2 through attempts at optical data storage3 and lasing4 to novel low‐noise detection techniques in various analytical methods such as electrophoresis5 or immunoassays,6 research in this area showed a real boost only with the technological advances in NIR imaging instrumentation. Thus, nowadays NIR dyes play a prominent role in many fields of medicinal chemistry and biotechnology, ranging from tomography7 through endoscopic imaging8 and tumor diagnostics9 to drug discovery10 and nucleic acid detection 11.…”
Section: Introductionmentioning
confidence: 99%
“…The development of functional dyes that absorb and emit in the red visible or near‐infrared (NIR) region of the optical spectrum has received increasing attention in the last decade. Although there has been considerable interest in NIR dyes since the early/middle of the last century,1 from advances in photography2 through attempts at optical data storage3 and lasing4 to novel low‐noise detection techniques in various analytical methods such as electrophoresis5 or immunoassays,6 research in this area showed a real boost only with the technological advances in NIR imaging instrumentation. Thus, nowadays NIR dyes play a prominent role in many fields of medicinal chemistry and biotechnology, ranging from tomography7 through endoscopic imaging8 and tumor diagnostics9 to drug discovery10 and nucleic acid detection 11.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of sulfonate groups to the dye structures greatly improves their solubility, and the addition of reactive groups such as isothiocyanate functionalities makes them suitable for use as covalent labels . Reported uses of NIR dyes for analytical applications include enzymatic assays, hydrophobicity, metal ion and pH probes, immunoassay applications, and as labels for DNA sequencing studies. …”
mentioning
confidence: 99%